Visualising uncertainty in flood maps: implications for decision-making in the Czech Republic - Kutnarová, Adéla (The University of Edinburgh, 2024)
This dissertation investigates the impact of different methods for visualising flooding uncertainty on decision-making within urban planning in the Czech Republic. While uncertainty is considered an important aspect of risk visualisation, its utility in influencing decision-making still needs to be explored. The primary objectives of this study were to assess whether varying visualisations of uncertainty lead to different decision-making choices and to evaluate the usability of these visualisations through participant tasks and usability testing. The evaluated visualisations included (1) a continuous uncertainty presentation, (2) an interactive overlay combining uncertainty with flooding certainty, and (3) a bar chart visualisation of uncertainty information derived from ensemble modelling. The findings indicate that the choice of visualisation method can significantly impact decision-making. However, even when visualisations did not lead to notably different choices, the visualisation design still substantially influenced the confidence with which decisions were made. The results underscore the importance of employing well-designed visualisations appropriate for specific applications.
Keywords: flooding; uncertainty; visualisation